Keanekaragaman Serangga Pengurai di Taman Gumi Banten Kawasan Hutan Desa Wanagiri, Buleleng - Riawan, I Made Oka (Jurnal Pendidikan Biologi Undiksha, 2023)
The Wanagiri Village Forest has a strategic role in conservation and tourism, and of course as a provider of offering materials through the availability of a diversity of vegetation in the forest, as well as a water conservation area. This study aims to determine the diversity and abundance of decomposer insects in the Gumi Banten Forest Park, Wanagiri Village, Buleleng, Bali so that sustainable conservation can be carried out. This study was an exploratory study and samples were collected using a pitfall trap with scattered sampling points and divided into four stations, each station consisting of 15 plots. The results of this study showed a diversity index of decomposers of 3.04 including the high category, and a relative abundance of 20.69.